Analisis Gambaran Durasi Kerja dan Masa Kerja dengan Kelelahan Kerja pada Driver Perusahaan Distributor Gas di Gresik - Yuna Kholbiatul Lutfia; Fariz Zuvil Arganata; Nafilatul Fitri (Calory Journal Medical Laboratory Journal, 2024)
Fatigue can be caused by personal stress factors. Based on observations and interviews, it is known that 5 drivers at the Gas Distributor Company in Gresik experienced work fatigue. The drivers complained that working hours that exceeded capacity limits and the pressure to continue making deliveries caused fatigue and increased turnover rates in the company. This study aims to analyze the description of work duration and work period with work fatigue in drivers of the Gas Distributor Company in Gresik. This study uses a quantitative descriptive method. The number of samples in this study was determined by a total sampling of 30 drivers. The method of obtaining research data was carried out by filling out a questionnaire. Based on the results of the analysis of the description of work period with work fatigue, 21 people with a work period of ≥5 years were obtained 5 people had high work fatigue and 4 people had very high work fatigue and 21 people <5 years were obtained 20 people had high work fatigue and 1 person had very high work fatigue. Analysis of the description of work duration with work fatigue showed that 6 people who worked <8 hours were obtained 3 people had high work fatigue and 3 people had very high work fatigue. Then from 24 people who worked ≥8 hours, 22 people had high work fatigue and 2 people had very high work fatigue. Based on the results of the work period analysis, most drivers worked <5 years as many as 20 drivers and in the results of the work duration analysis, most drivers worked ≥8 hours as many as 22 drivers.